Progressiva koalitioner, (inter)nationella influenser och kunskapsmätningar i reformarbetet med svensk läroplan, ca 1930–1950 - Lundahl, Christian (Nordic Journal of Educational History, 2014)
Progressive Coalitions, (Inter)National Influences and Knowledge Assessments in Swedish Curriculum Reform, ca 1930–1950 Insight gained through assessments and international precedents are two strategies typically used to reform national curricula in modern educational systems. The present article illustrates how a progressive movement in Sweden used its participation in the International Examination Inquiry, not as source of ideas or methods, but as an experience of urbanity that lent credence to its proposed solutions to national educational issues. It will be shown how this movement used the IEI to promote and establish a particular institute in Sweden, the Swedish Institute for Educational Psychology (SPPI), an institute that came to re/produce a psychology-laden educational termino-logy directly affecting Swedish curricula for years to come.